Kilka uwag na temat zasad działania Komisji Odwoławczej Agencji ds. Współpracy Organów Regulacji Energetyki - Swora, Mariusz (Studia Prawa Publicznego, 2022)
The Board of Appeal (BoA) of the Agency for the Cooperation of Energy Regulators (ACER) belongs to the category of appeal bodies hearing appeals against the deci-sions of EU administrative agencies. ACER BoA acts on the basis of legal framework dedicated to the Agency, while the rules of conduct before the Board are regulated by internal rules of procedure. These regulations are practically the only legal acts regulating the procedure before the BoA, as the EU has not adopted a single ad-ministrative code that would regulate the procedure before such bodies, inter alia. The BoA is a specialised body responsible for adjudicating complex cases in the ﬁeld of the EU common energy market related to the implementation of European network codes. The CJEU (General Court) sought to dispel any doubts concerning the rules of adjudication of the BoA in the ACER v. Aquind judgment by expressing a number of views on the scope and standard of adjudication, but even in the light of this judgment, a number of matters remain unclear. Consequently, it is all the more urgent to adopt a clear procedural and systemic framework governing the functioning of the BoA.